THE RELATIVITY OR NOT OF THE CONSTITUTIONAL RIGHT TO SILENCE: FROM THE SUBDIVISION AND INTERSECTION BETWEEN PUBLIC LAW AND PRIVATE LAW TO AN INTER AND MULTIDISCIPLINARY CONSTRUCTION - Bonizzato, Luigi; Silveira Ardente, Luciana; Esteves Moulin, Isabelle (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2024)
This Article brings out specific and deepened approach to the right to silence, examining the hypothesis according to which the aforementioned constitutional and fundamental right would be relative or not. With the aim of scrutinizing the right to silence, based on an investigative stimulus provoked by a concrete situation resulting from a court decision, the present study starts from the analysis of the idea of ​​complementarity and interdisciplinarity between Public Law and Private Law, as well as among varied branches of law. This is because the right to silence itself, better explored in the second chapter, depending on interpretations and theoretical developments, can gravitate and transit, sometimes more, sometimes less, along with Public and Private Laws. And because the right to silence is, at the same time, another right to freedom found in the 1988 Brazilian Constitution, its specific research in this article is preceded by directed evaluation of other fundamental freedoms, such as the expression of thought, among others developed in the text. Finally, considering the analytical-deductive methodology used, supported by theories, legislation, legal norms and current concrete decisional examples, this research revisits classical themes, but strengthens and innovates them with a peculiar and specific epistemological and hermeneutic exercise.